Therapy Dogs in Educational Settings: Guidelines and Recommendations for Implementation - Grové, Christine; Henderson, Linda; Lee, Felicia; Wardlaw, Phoebe (Frontiers in Veterinary Science, 2021)
Therapy dogs in educational settings have gained increase traction in recent years. Despite its potential benefits and popularity, there remain concerns of perceived risks such as sanitation, allergies, and safety issues, as well as a lack of guidelines, regulations and support resources available to school staff. Research is further lacking into the implementation process of therapy dog programs in educational settings. To construct a set of recommendations for school staff to achieve successful implementation of a therapy dog program, the present study investigated the perceived facilitative and impeding factors when implementing a therapy dog program. A total of 13 school staff and 2 coordinators from therapy dog organisations took part in an open-ended online survey and/or a semi-structured interview over the phone, with the aim of gathering their perspectives of implementing a therapy dog program in schools. The thematic analysis of the data indicated facilitative factors such as program flexibility, whole-school support, the need for communication and training for all staff, as well as dog welfare. Successful implementation of therapy dogs in an education setting appear to revolve around (1) flexibility of the dog therapy program to target school’s needs, (2) qualities of program instigator, (3) whole-school support, (4) communication, training and education, (5) considerations for dog’s welfare. Key barriers identified included a high workload, lack of guidelines on processes, lack of support from the school community, as well as the need for better understanding of the role of a therapy dog. The results highlighted the importance of a whole-school effort when implementing a therapy dog program, as well as the need for guidelines for assessing school readiness, key factors for consideration, and strategies to overcome challenges associated with program implementation.